Effects of Half-Somersault and Brandt-Daroff exercise on dizziness, fear of fall and quality of life in patients with posterior canal benign paroxysmal positional vertigo: a randomised control trial - Muhammad Jaffar; Misbah Ghous; Mahnoor Ayaz; Amir Afzal Khan; Asif Akbar; Farhan Haleem (Journal of the Pakistan Medical Association, 2022)
The aim of this study was to compare the effects of Half-Somersault and Brandt-Daroff exercises on dizziness, fear of fall, and quality of life in patients with posterior canal benign paroxysmal positional vertigo (PC-BPPV). This study was conducted from July 2020 to November 2020. A total of 20 patients were enrolled in the study, through sealed envelope method, and assigned to two groups, A and B (10 in each). Vestibular activity and participation measure and Fall Efficacy Scale (FES) were used. The mean age of the patients was 36.70±11.58 years. There was a significant (p=0.05) difference between the Vestibular activities and participation measure (VAP) score at post intervention and Fall Efficacy Scale (FES) (p<0.05) between the groups. Within group analysis showed significant results (p=0.01). This study concluded that both manoeuvers are significantly effective in the treatment of PC-BPPV, but patients treated with Brandt-Daroff exercises reported more improvement in terms of quality of life and residual dizziness compared to the Half Somersault group. Key words: Benign paroxysmal positional vertigo, dizziness, vestibular rehabilitation.